SYSTEM ANALYSIS PROCEDURE FORMALIZATION BY CHOOSING MATERIAL AND REQUIREMENTS TO PART STRENGTHENING TREATMENT IN INTEGRATED CAD/CAM - Mikhail E. Popov; Andrey M. Popov; Abuharb Mohammad (Advanced Engineering Research, 2012)
The problem on the procedure formalization of the optimal selection of the constructional material and the requirements to part strengthening treatment in the integrated CAD/CAM is stated.